The effect of vitamin D and vitamin A supplementation on T cell levels of patients with pneumosepsis: A double-blind, randomized clinical trial - Abolfazl Jokar; Alireza Sistani; Ghasem Mosayebi; Atefeh Poyandeh (Clinical Nutrition Open Science)
Summary: Background & aims: Pneumosepsis is a global healthcare challenge associated with substantial morbidity and mortality rates. Its pathogenesis involves intricate interactions among host factors, pathogens, and immune dysregulation. Vitamins A and D are crucial for immune function, acting as regulators and cofactors in immune cell development and function. Given these roles, this study aimed to assess the impact of combined vitamin D and A supplementation on T cell levels in pneumosepsis patients. Methods: This double-blind clinical trial enrolled 84 pneumosepsis patients who were randomly assigned to four groups after demographic data collection. Intervention: Group 1 received standard treatment plus 300,000 IU of vitamin D and 50,000 IU of vitamin A. Group 2 received standard treatment plus 300,000 IU of vitamin D. Group 3 received standard treatment plus 50,000 IU of vitamin A. Group 4 received only standard treatment. Main outcome measures: Vital signs were monitored every 6 hours, and T-cell count, ESR, CRP, creatinine, urea, and uric acid levels were assessed at 0, 24, 48, and 72 hours. Results: Initially and one day post-intervention, vital signs and blood factors showed no significant differences among the groups. However, on days two and three post-intervention, the combined vitamin D and A group exhibited significantly lower levels compared to other groups. Lymphocytes expressing CD3+, CD4+, CD25+, CD3,4+, and CD3,4,25+ markers significantly differed in the combined vitamin A + D group versus the control. No significant differences were noted in lymphocyte percentages between the combined vitamin A + D group and those receiving only vitamin D or A. Conclusion: This study underscores the potential benefits of concurrent vitamin D and A supplementation in reducing symptoms among pneumosepsis patients, particularly in modulating key physiological parameters and immune responses. Trial registration: This study is registered on Iranian Registry of Clinical Trials (IRCT) under identifieron IRCT20130424013110N10. (The registration date: Jul 6, 2020).